The Implementation of Morning Journals as a Teacher’s Strategy in Improving Early Childhood Literacy - Moh. Taufiq; Nurifah Nurifah (Sustainable, 2025)
This study aims to describe teacher strategies in stimulating early childhood literacy through morning journal habituation activities at KBTK Islam Insan Kamil Tuban. Literacy is one of the basic competencies that need to be developed from an early age as a foundation for academic abilities at the next level. This study uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The results show that morning journal habituation can stimulate children's literacy skills in the aspects of listening, speaking, reading, and writing. Teachers act as facilitators by creating a pleasant learning atmosphere, providing examples, and guiding children to write and draw based on daily experiences. Morning journal habituation also fosters discipline, self-confidence, and children's ability to express ideas. Thus, morning journal activities are effective as a strategy to improve early childhood literacy that is contextual and enjoyable.